(untitled) (Ha Noi, 2015)
This work contains a verbatim account of the presentations and debates from the plenary sessions and workshops that took place from 21th to 29th July 2014 at the University of Da Lat on the topic of "A Glance at Sustainable Urban Development". Four main areas of reflection are prioritised in the framework of the thematic workshops: (i) tools and models for urban and territorial planning; (ii) tools and models for understanding and exploiting urban spatial dynamics; (iii) the city and socio-spatial inequalities; (iv) training for field studies: practices, networks and strategies linked to market gardening in peri-urban areas.
Keywords: Phát triển cộng đồng,Community development; Phát triển đất nước,Developing countries